Circulating hematopoietic progenitor cells in patients affected by chornobyl accident - Bilko, N.M.; Dyagil, I.S.; Russu, I.Z.; Bilko, D.I. (Experimental Oncology, 2016)
High radiation sensitivity of stem cells and their ability to accumulate sublethal radiation damage provides the basis for investigation of hematopoietic progenitors using in vivo culture methodology. Unique samples of peripheral blood and bone marrow were derived from the patients affected by Chornobyl accident during liquidation campaign. Aim: To investigate functional activity of circulating hematopoietic progenitor cells from peripheral blood and bone marrow of cleanup workers in early and remote periods after the accident at Chornobyl nuclear power plant (CNPP). Materials and Methods: The assessment of the functional activity of circulating hematopoietic progenitor cells was performed in samples of peripheral blood and bone marrow of 46 cleanup workers, who were treated in the National Scientific Center for Radiation Medicine of the Academy of Medical Sciences of Ukraine alongside with 35 non radiated patients, who served as a control. Work was performed by culturing peripheral blood and bone marrow mononuclear cells in the original gel diffusion capsules, implanted into the peritoneal cavity of CBA mice. Results: It was shown that hematopoietic progenitor cells could be identified in the peripheral blood of liquidators of CNPP accident. At the same time the number of functionally active progenitor cells of the bone marrow was significantly decreased and during the next 10 years after the accident, counts of circulating progenitor cells in the peripheral blood as well as functionally active hematopoietic cells in bone marrow returned to normal levels. Conclusion: It was shown that hematopoietic progenitor cells are detected not only in the bone marrow but also in the peripheral blood of liquidators as a consequence of radiation exposure associated with CNPP accident. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.